Spatio-Temporal Analysis of Agricultural Development A Block-Wise Study of Dehradun District - Khan, Kazma; khalil, Lubna (International Journal of Geography and Geology, 2013)
In the present paper an attempt has been made to find out the spatio-temporal variation in the adaptation of improved agricultural practices to ascertain the level of agricultural development in Dehradun district of Uttarnchal. The study is based on the block-wise published data obtained from Statistical Bulletin of Dehradun district. The spatio-temporal pattern of agricultural development is determined with the help of thirteen variables. Beside this, the analyses have been carried out by transforming and combining the data related to thirteen variables, using ‘Z’ score to get the composite score. On the basis of Composite Score, developments of blocks have been categorized into three categories i.e. high, medium and low. Results of the aforesaid analysis shows that the modern technological inputs have reciprocal relationship with agricultural development in the study area.